Small bowel obstruction in a 42-year-old patient? Be aware of Meckel’s diverticulum - Mulita, Francesk; Verras, Georgios-Ioannis; Tchabashvili, Levan; Liolis, Elias; Kaplanis, Charalampos; Perdikaris, Ioannis; Maroulis, Ioannis (Gastroenterology Review/Przegląd Gastroenterologiczny, 2022)
Meckel’s diverticulum (MD) is the most common congenital anomaly of the gastrointestinal tract, and according to several studies its prevalence is about 0.6–4% [1]. The exact location of MD is mentioned in the literature and in textbooks, and its characteristics usually follow the rule of twos: 2% of the general population, 2 feet proximal to the ileocecal valve, 2 inches in length, and 2 : 1 male: female ratio [2].